Imaging approaches and radiomics: toward a new era of ultraprecision radioimmunotherapy?. Issue 7 (6th July 2022) - Sun, Roger; Henry, Théophraste; Laville, Adrien; Carré, Alexandre; Hamaoui, Anthony; Bockel, Sophie; Chaffai, Ines; Levy, Antonin; Chargari, Cyrus; Robert, Charlotte; Deutsch, Eric
Abstract : Strong rationale and a growing number of preclinical and clinical studies support combining radiotherapy and immunotherapy to improve patient outcomes. However, several critical questions remain, such as the identification of patients who will benefit from immunotherapy and the identification of the best modalities of treatment to optimize patient response. Imaging biomarkers and radiomics have recently emerged as promising tools for the non-invasive assessment of the whole disease of the patient, allowing comprehensive analysis of the tumor microenvironment, the spatial heterogeneity of the disease and its temporal changes. This review presents the potential applications of medical imaging and the challenges to address, in order to help clinicians choose the optimal modalities of both radiotherapy and immunotherapy, to predict patient's outcomes and to assess response to these promising combinations.